Congenital Hepatic Cyst. (7th April 2017) - Recinos, Aldo; Zahouani, Tarik; Guillen, Juan; Rajegowda, Benamanahalli
Congenital hepatic cyst is a rare and nonsymptomatic condition in infants and children. Its incidence is 2.5% in the postnatal life with a much lower incidence in the prenatal period. Incidental finding on antenatal imaging is the most common presentation. We present a case of a newborn in whom fetal ultrasound detected a cyst within the fetal liver. Postnatal imaging revealed a liver cyst in the right lobe of the liver, with no other intrahepatic structure affected. Liver function tests were abnormal, but the patient was asymptomatic. Posterior follow-up imaging showed a minor decrease in size. Management of congenital hepatic cyst is usually conservative, done with periodic ultrasound monitoring. However, surgical treatment is the mainstay of treatment when hydrops, progressive enlargement, hemorrhage, torsion, or compression of adjacent structures occurs. Malignant transformation can occur, but it is extremely rare. Partial or total removal of the cyst is the preferred treatment in neonates with a large lesion.